The Effectiveness of The E-Archives Program in Improving Administrative Performance in the Organizational Section of the Surabaya City Regional Secretariat - Elizabeth Clara Sitanggang; Vidya Imanuari Pertiwi (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Digital transformation in public administration has encouraged the implementation of electronic records management systems as an effort to improve efficiency and the quality of administrative services. This study analyzes the effectiveness of the E-Archive Program in enhancing administrative performance at the Organizational Division of the Regional Secretariat of Surabaya City. Employing a descriptive qualitative approach with data collection techniques including observation, semi-structured interviews, and documentation, the study focuses on four aspects based on the model of Penn, Pennix, and Coulson, namely: information systems, user competence, technological infrastructure, and regulations and standard operating procedures (SOPs). The findings indicate that the E-Archive system effectively improves work efficiency, particularly in accelerating records retrieval, ensuring the accuracy of document distribution, and enhancing the orderliness of document management. Based on these findings, it can be concluded that the E-Archive Program has made a significant contribution to improving administrative performance in the relevant institution.